2146. Efficacy and Patterns of Antimicrobial Prophylaxis for Gunshot Wound Infection in a South African Hospital Setting: a Prospective Study Using Propensity Score-Based Analyses. (26th November 2018) - Visbeek, Martti; De Boer, Mark; Steyn, Elmin; Taljaard, Jantjie
Abstract: Background: In countries with a high incidence of interpersonal violence involving firearms, gunshot wound (GSW) related infection is a regular and serious complication. However, limited evidence supports the efficacy of antimicrobial prophylaxis (AP) in resource restricted areas. At Tygerberg Hospital, South Africa, it is standard care for GSW patients to receive one dose of amoxicillin-clavulanic acid or cefazolin to prevent GSW-related infection. For various reasons protocol adherence can be suboptimal. This study aimed to assess the efficacy in regard to reduction of in-hospital GSW infection and to identify opportunities for practice improvement. Methods: All GSW patients admitted between October 12, 2017 and January 3, 2018 were prospectively included. Data regarding injury characteristics, circumstances of the incident, type of AP and surgery were obtained. The occurrence of in-hospital GSW infection was monitored over 30 days or until discharge, whichever occurred first. Univariate analyses were performed to compare characteristics of patients with- and without prophylaxis. A multivariate logistic regression model was used to obtain propensity scores. To correct for confounding, propensity score matching (PSM) and inverse probability weighting (IPW) methods were used to assess the effect of AP on the occurrence of GSW infection. Results: A total of 165 consecutive patients were included. Hundred-and-three patients received AP according to protocol within 12 hours after admission, 62 patients did not. Only 63.9% of the multi-GSW patients and 69.1% of the patients with a fracture received AP. These conditions were associated with an uncorrected relative risk for infection of 2.08 (95% CI 1.32–3.26) and 1.81 (95% CI 1.08–3.04), respectively. PSM showed a reduced in-hospital GSW infection risk of 12% (95% CI 0.2–24%, P = 0.046) with AP. IPW showed that AP reduced the risk for infection by 14% (95% CI, 3–27%, P = 0.015). Conclusion: Providing antimicrobial prophylaxis to GSW patients appeared to result in a clinically relevant lower risk of in-hospital GSW infection. In this study setting, optimization of provision of AP for all patients with multiple GSW's or a GSW-related fracture are opportunities for reduction of GSW infection. Disclosures: All authors: No reported disclosures.